Hyperammonaemia and associated factors in unprovoked convulsive seizures: A cross-sectional study. (December 2016) - Sato, Kenichiro; Arai, Noritoshi; Omori, Aki; Hida, Ayumi; Kimura, Akio; Takeuchi, Sousuke
Highlights: Hyperammonaemia is frequently seen in unprovoked convulsive seizure patients. Independent factors associated with hyperammonaemia were identified. These factors were consistent with the muscle contraction and/or respiratory failure. Further study of the possible influence of ammonia on seizure patients is expected. Abstract: Purpose: Hyperammonaemia is frequently observed in patients who have experienced convulsive seizures. Although excessive muscle contraction is presumed to be responsible for the elevated levels of ammonia, the underlying mechanism is poorly understood. The present study aimed to identify the independent factors associated with ammonia elevation using large-scale multivariate analysis. Methods: We conducted a cross-sectional study involving 379 adult patients who had been transported to our emergency department and treated for unprovoked convulsive seizures between August 2010 and September 2015. Elevation of venous plasma ammonia levels was set as the primary endpoint, and patients' clinical and laboratory data were obtained. Those with severe liver dysfunction, known hepatic encephalopathy, or convulsions due to cardiovascular or psychogenic causes, and those taking valproate were excluded. Results: Using a cut-off value of 50 μg/dL, 183 patients (48.3%) were found to have elevated levels of plasma ammonia. Four factors were identified as independent variables associated with hyperammonaemia following seizures: elevated venous lactate, lowered venous pH, sex (male), and longer duration of convulsion. Conclusions: The results of the present study revealed independent factors associated with hyperammonaemia following unprovoked convulsive seizures in a larger scale and with more plausible statistical analysis. The authors further suggest that the excessive skeletal muscle contraction and/or respiratory failure during/after convulsive seizure may be the primary mechanism of hyperammonaemia.